LATEST PALEOCENE-EARLIEST EOCENE CYCLOSTRATIGRAPHY: USING CORE PHOTOGRAPHS FOR RECONNAISSANCE GEOPHYSICAL LOGGING - Cramer B.S. (My University, 2001)
I present a new method for reconnaissance cyclostratigraphic study of continuously cored boreholes: the generation of detailed sediment color logs by digitizing Ocean Drilling Program (ODP) core photographs. The reliability of the method is tested by comparison with the spectrophotometer color log for the uppermost Paleocene-lowermost Eocene section (Chron C24r) at ODP Hole 1051A. The color log generated from Hole 1051A core photographs is essentially identical to the spectrophotometer log. The method is applied to the Chron C24r section at Holes 1051A and 690B, producing the first high-resolution geophysical log for the latter section. I calculate astronomically calibrated durations between bio- and chemostratigraphic events within Chron C24r by correlating the cyclostratigraphies for Holes 1051A and 690B. These durations are significantly different from previous estimates, indicating that the chronology of events surrounding the Paleocene/Eocene boundary will have to be revised. This study demonstrates that useful geophysical logs can be generated from digitized ODP and DSDP core photographs. The method is of practical use for sections lacking high-resolution logs, as is the case for most lower Paleogene sections.
Keywords: PHOTOGRAPHS; COLOR; CYCLES; CYCLOSTRATIGRAPHY; PALEOCENE; EOCENE; Cenozoic::Paleogene::Eocene; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Эоцен; Кайнозой::Палеоген::Палеоцен